Pengaruh Brand Image, Store Atmosphere, dan Gaya Hidup Terhadap Keputusan Pembelian pada Kopi 20 - Rahman, Rafi Aulia; Warganegara, Tri Lestira Putri (Journal of Information System, Applied, Management, Accounting and Research, 2026)
Kopi 20 is influenced by independent variables, namely brand image as X1, store atmosphere as X2, and lifestyle as X3, both partially and simultaneously. The methodology used is quantitative research. The field survey approach used in this study is direct data collection from Kopi 20 consumers by sending online questionnaires using Google Forms. The quantitative research methodology used in the study population is Kopi 20 consumers, which are then estimated using the Lemshow formula to obtain a sample of 100 responses. The questionnaire for this study is based on a Likert scale with a score range of 1 to 5. The data were analyzed using SPSS version 27 by finding many independent factors, including brand image, price, and promotion, which are considered to influence the dependent variable, purchasing decisions. Validity, reliability, multiple linear regression, partial, simultaneous, and coefficient of determination tests were used in this study. The purpose of this test was to evaluate the relationship between the elements influencing purchasing decisions and determine the extent of each aspect's influence on purchasing decisions at Kopi 20. The results of this study indicate that purchasing decisions at Kopi 20 are influenced by the independent variables, namely store atmosphere (X2), and brand image (X1), but have no effect on purchasing decisions at Kopi 20.